2009
DOI: 10.1128/aem.02147-08
|View full text |Cite
|
Sign up to set email alerts
|

Host-Directed Evolution of a Novel Lactate Oxidase in Streptococcus iniae Isolates from Barramundi ( Lates calcarifer )

Abstract: In Streptococcus iniae, lactate metabolism is dependent upon two proteins, lactate permease that mediates uptake and lactate oxidase, a flavin mononucleotide-dependent enzyme that catalyzes oxidation of ␣-hydroxyacids. A novel variant of the lactate oxidase gene, lctO, in Australian isolates of S. iniae from diseased barramundi was found during a diagnostic screen using LOX-1 and LOX-2 primers, yielding amplicons of 920 bp instead of the expected 869 bp. Sequencing of the novel gene variant (type 2) revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Strains were recovered from stock without defrosting and grown on Columbia agar base containing 5% defibrinated sheep blood (Oxoid, Australia) at 28°C for 24 to 48 h. Where isolates were obtained from farm cases through veterinarians, histopathology was performed by the veterinary laboratories using standard techniques. Identity of strains was confirmed by diagnostic PCR as previously described (20,27) and by sequencing the 16S rRNA gene (26,27).…”
Section: Methodsmentioning
confidence: 99%
“…Strains were recovered from stock without defrosting and grown on Columbia agar base containing 5% defibrinated sheep blood (Oxoid, Australia) at 28°C for 24 to 48 h. Where isolates were obtained from farm cases through veterinarians, histopathology was performed by the veterinary laboratories using standard techniques. Identity of strains was confirmed by diagnostic PCR as previously described (20,27) and by sequencing the 16S rRNA gene (26,27).…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplification was performed in a 50-µL reaction volume containing DNA template (80 ng) using the LOX 1/2 primer set, which specifically amplifies the gene encoding lactate oxidase, producing an 870-bp (Mata et al, 2004b) or 920-bp (Nawawi et al, 2009) …”
Section: Pcr Analysis Of S Iniae In Sludgementioning
confidence: 99%
“…S. iniae has been reported to infect a large variety of cultured fish species under salinities ranging from fresh water to marine water (Salati, 2011;Nawawi et al, 2009). Several PCR-based assays have been developed for the detection of S. iniae (Berridge et al, 1998;Lau et al, 2004;Mata et al, 2004a,b;Zlotkin et al, 1998).…”
mentioning
confidence: 97%
“…Lactate metabolism has previously been shown to be variable in fish pathogenic streptococci. In a case of Streptococcus iniae infection in barramundi (Lates calcarifer), molecular epidemiology revealed a novel lactate oxidase, which was confined to a single farm in Northern Territory with extreme tidal flow (Nawawi et al, 2009). The authors suggested an evolutionary advantage for these strains of S. iniae to have a more efficient enzyme under conditions where lactate concentration is high (Nawawi et al, 2009).…”
Section: Discussion Reduced Metabolic Capacities In the Piscine Isolatesmentioning
confidence: 98%
“…In a case of Streptococcus iniae infection in barramundi (Lates calcarifer), molecular epidemiology revealed a novel lactate oxidase, which was confined to a single farm in Northern Territory with extreme tidal flow (Nawawi et al, 2009). The authors suggested an evolutionary advantage for these strains of S. iniae to have a more efficient enzyme under conditions where lactate concentration is high (Nawawi et al, 2009). In common with S. iniae and other fish pathogenic steptococci, GBS are essentially systemic blood pathogens highly adapted to survive and proliferate within the circulatory system prior to colonisation of the central nervous system (CNS).…”
Section: Discussion Reduced Metabolic Capacities In the Piscine Isolatesmentioning
confidence: 99%